What do stakeholders perceive as success in large scale environmental monitoring design? - Dai, Xiaoyan; Webb, J. Angus; Horne, Avril C. (Frontiers in Environmental Science, 2025)
The decline in global freshwater biodiversity demands urgent action. Governments are attempting to use environmental management to partly restore degraded ecosystems through targeted interventions. Designing monitoring programs to assess the success of these large-scale management programs is challenging. There is much literature addressing the technical challenges of monitoring program design, and many of these studies acknowledge limitations in current implementation. In this study, we examine the perspectives of those managers and scientists involved in designing a large-scale monitoring program and their understanding of what makes a monitoring program successful. We focus on an environmental flow monitoring program (the Flow Monitoring, Evaluation and Research program—Flow-MER—in Australia). Through semi-structured interviews and surveys, we aimed to identify what those involved consider to be “success” for monitoring projects. The outcomes highlight that—consistent with literature—clear objectives are considered pivotal to project success. However, despite this recognition, challenges in establishing clear objectives were identified as a pressing concern for the Flow-MER program. The survey results included a recurring emphasis from participants on the importance of consistent, long-term datasets. There was less clarity around how to balance monitoring design to both demonstrate management success and address key scientific uncertainties as part of adaptive management and monitoring. The findings show that while there is broadly a common understanding of success for large monitoring design, major monitoring programs such as Flow-MER continue to fall short in successful design. The approach to surveying those involved in the monitoring program, along with their articulated understanding of program shortfalls, both provide insights on how to improve design and implementation of future large-scale monitoring programs. In particular, we highlight the need for managers to establish clear objectives and invest in effective communication strategies.